Have urinary function outcomes after radical prostatectomy improved over the past decade?. Issue 5 (1st November 2021) - Clements, Matthew B.; Gmelich, Caroline C.; Vertosick, Emily A.; Hu, Jim C.; Sandhu, Jaspreet S.; Scardino, Peter T.; Eastham, James A.; Laudone, Vincent P.; Touijer, Karim A.; Coleman, Jonathan A.; Vickers, Andrew J.; Ehdaie, Behfar
Abstract : Background: Changes in surgical technique and postoperative care that target improvements in functional outcomes are widespread in the literature. Radical prostatectomy (RP) is one such procedure that has seen multiple advances over the past decade. The objective of this study was to leverage RP as an index case to determine whether practice changes over time produced observable improvements in patient‐reported outcomes. Methods: This study analyzed patients undergoing RP by experienced surgeons at a tertiary care center with prospectively maintained patient‐reported outcome data from 2008 to 2019. Four patient‐reported urinary function outcomes at 6 and 12 months after RP were defined with a validated instrument: good urinary function (domain score ≥ 17), no incontinence (0 pads per day), social continence (≤1 pad per day), and severe incontinence (≥3 pads per day). Multivariable logistic regressions evaluated changes in outcomes based on the surgical date. Results: Among 3945 patients meeting the inclusion criteria, excellent urinary outcomes were reported throughout the decade but without consistent observable improvements over time. Specifically, there were no improvements in good urinary function at 12 months ( P = .087) based on the surgical date, and there were countervailing effects on no incontinence (worsening; P = .005) versus severe incontinence (improving; P = .003). Neither approach (open, laparoscopic, or robotic), nor nerve sparing, nor membranous urethral length mediated changes in outcomes. Conclusions: In a decade with multiple advances in surgical and postoperative care, there was evidence of improvements in severe incontinence, but no measurable improvements across 3 other urinary outcomes. Although worsening disease factors could contribute to the stable observed outcomes, a more systematic approach to evaluating techniques and implementing patient selection and postoperative care advances is needed. Lay Summary: Although there have been advances in radical prostatectomy over the past decade, consistent observable improvements in postoperative incontinence were not reported by patients. To improve urinary function outcomes beyond the current high standard, the approach to studying innovations in surgical technique needs to be changed, and further development of other aspects of prostatectomy care is needed. Abstract : Over a decade of advances in radical prostatectomy surgical technique, quality improvement, and postoperative management, recent improvements were detected in severe incontinence but not in 3 other urinary outcomes, including pad‐free status. This suggests that a more systematic approach to evaluating surgical techniques and implementing postoperative care advances is needed to foster observable improvements.